Research on the Blended Teaching Reform of Tax-related Legal Courses Based on the Case Teaching Method in the Context of Tax Benefits for Agriculture - Yin, Yanqin (Journal of Research in Vocational Education, 2025)
With the in-depth promotion of the rural revitalization strategy, the tax incentives to help farmers have been strengthened. The demand for legal talents is becoming more and more urgent. However, the traditional teaching mode of “Tax-related Laws” is difficult to In order to meet the demand for talent training in the new era, reform is urgently needed. The hybrid teaching reform path of tax-related law courses based on case teaching method. Combined with online and offline teaching resources, the tax incentive cases to help farmers improve students’ practical application of tax policies. The research results show that this model can not only effectively make up for the shortcomings of traditional teaching, but also better Cultivate students’ ability to deal with complex real-life problems and enhance their comprehensive abilities and practical experience. Including updating teaching content, developing rich multimedia teaching resources, designing flexible and diverse teaching methods, and Adopt a diversified assessment system. Through these reform measures, Aims to improve the teaching effect of the course and cultivate high The future research will further explore the Further explore the deep integration of case teaching method and hybrid teaching mode, and expand the course content to help students Comprehensive understanding of the role of tax policy in agriculture and rural development.